Bridging the Gap between Public and Stakeholder Interests in Sustainable Energy Policy: A Meta-Analysis Study - Pathiranage, Heshan Sameera Kankanam (Current Topics on Business, Economics and Finance Vol. 6, 2023)
The aim of this study is to explore the interests and perceptions of stakeholders and the general public on policies and technologies that promote energy sustainability. To accomplish this aim, we have set three attainable objectives. The first objective is to investigate stakeholders' opinions on new policies and technologies that promote sustainable energy. The second objective is to comprehend why the public may be reluctant to embrace new technologies and policies that promote energy sustainability. The third objective is to determine feasible approaches to serve the interests of stakeholders while mitigating the climatic impact of unsustainable energy sources and obtaining public acceptance. In this meta-analysis investigation, we selected 23 studies that met our rigorous inclusion and exclusion criteria. We analyzed the extracted data using HOMA and MARA. Our findings indicate that stakeholders are primarily interested in assuring energy autonomy and promoting renewable energy solutions to address the environmental impact of fossil fuels. On the other hand, the public is sensitive to procedural justice, distribution justice, placement, and trust. Our study emphasizes the significance of aligning the interests of stakeholders and the public to develop feasible and acceptable policies to drive sustainable development.